2014
DOI: 10.1016/j.appet.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Initial evidence that GLP-1 receptor blockade fails to suppress postprandial satiety or promote food intake in humans

Abstract: Glucagon-like peptide 1 (GLP-1) has incretin effects that are well-documented, but the independent role of GLP-1 action in human satiety perception is debated. We hypothesized that blockade of GLP-1 receptors would suppress postprandial satiety and increase voluntary food intake. After an overnight fast, 8 normal weight participants (7 men, BMI 19–24.7 kg/m2, age 19–29 yr) were enrolled in a double-blind, placebo-controlled, randomized crossover study of the GLP-1 antagonist Exendin-[9–39] (Ex-9) to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In both groups of respondents, levels of GLP-1 and CCK did not correlate significantly with the VAS Q1 (hunger) and VAS Q2 (fullness). This finding is supported by Melhorn et al, who reported that blocking GLP-1 receptors failed to decrease appetite and increased the food intake in humans and that it was not related to the personal response for satiety (VAS) (31). There are limitations in this research that need to be considered, such as the significant difference in CCK levels between the obese and healthy-weight respondents at baseline that might influence the final intervention result.…”
Section: Discussionsupporting
confidence: 62%
“…In both groups of respondents, levels of GLP-1 and CCK did not correlate significantly with the VAS Q1 (hunger) and VAS Q2 (fullness). This finding is supported by Melhorn et al, who reported that blocking GLP-1 receptors failed to decrease appetite and increased the food intake in humans and that it was not related to the personal response for satiety (VAS) (31). There are limitations in this research that need to be considered, such as the significant difference in CCK levels between the obese and healthy-weight respondents at baseline that might influence the final intervention result.…”
Section: Discussionsupporting
confidence: 62%
“…With respect to criterion 6 of TABLE 2, GLP-1R antagonism with exendin(9 -39) failed to increase test meal size in healthy humans tested under five distinct experimental conditions (492,721) and in two groups of RYGB patients tested 3-12 mo after surgery, when their mean BMI was ϳ34 kg/m 2 (737). In contrast, exendin(9 -39) did increase test meal size in one of the RYGB-patient groups in a preoperative test (737).…”
Section: Eatingmentioning
confidence: 99%
“…In addition, in rats, central endogenous GLP-1 affects food intake and body weight [ 11 , 18 ]. In humans, the effects of endogenous GLP-1 on prospective food consumption have been demonstrated [ 17 ], but changes in food intake could not be detected in a small pilot study [ 28 ]. Regarding the effects of endogenous GLP-1 on the CNS in humans, an association between postprandial increases in GLP-1 levels and the cerebral blood flow in areas involved in feeding behaviour has been observed [ 29 ], but our study is the first to investigate the effects of endogenous GLP-1 in an interventional setting.…”
Section: Discussionmentioning
confidence: 99%